A Transmission Control Protocol for Wireless Sensor Network - Sharma, Neelam; Singh, Karan; Singh, B M (International Journal of Integrated Engineering, 2020)
Wireless Sensor Network (WSN) is a hot area of research which is useful in countless applications in various fields of engineering and technology. In WSN wireless nodes are dispersed in a well confined area, and most of the times are static once they are deployed. These nodes are battery operated and their energy goes down as they transmit beacon or informative packets. In past many routing protocols are proposed which tries to minimize the energy dissipation by using various approaches. Till date in proposed protocols information is transmitted in each round, however in many applications such frequent information/update is not desirable, therefore to restrict transfer of packets in each round in this paper a transmission control protocol is proposed, where by varying the load, transfer of packets can be controlled, and this mechanism reduces the dissipation of energy and thus improves, stability period, network lifetime and throughput. The performance evaluation of the proposed scheme is done using MATLAB software and keys features of proposed protocol are highlighted along with simulation results